AB0322 Preliminary Data on The Introduction of The Infliximab Biosimilar (CT-P13) To A Real World Cohort of Rheumatology Patients. (15th July 2016) - Sheppard, M.; Hadavi, S.; Hayes, F.; Kent, J.; Dasgupta, B.
Abstract : Background: Infliximab is a chimeric monoclonal antibody against tumour necrosis factor alpha (TNF-α), used to treat autoimmune diseases such as rheumatoid arthritis, ankylosing spondylitis and psoriatic arthritis. 1 In 2015 NICE recommended the use of a new less expensive biosimilar CT-P13 (Remsima™; Inflectra™), based on its efficacy, safety and quality comparable to the reference infliximab product. 2 At Southend University Hospital NHS Foundation Trust, the use of CT-P13 has reduced treatment costs and allowed significant cost savings compared with reference infliximab. Objectives: To review patient outcomes and estimate the cost savings of using CT-P13 as compared with reference infliximab. Methods: Information packs were sent out to patients to inform them of the intended switch from Infliximab to CT-P13. Their understanding was further reinforced in a face-to-face session with the biologics pharmacist and any concerns were addressed. Additionally patients had access to a dedicated email account which was set up to deal with their queries. Written consent was obtained from patients prior to the switch. Patients were carefully monitored during the first infusion of CT-P13 and were advised to contact the rheumatology department if they developed any undue side-effects or loss of disease control. All eligible patients were offered a chance to recruit to BSR Biologics Register. All side-effects were reported to MHRA. Results: 25 patients consented to the switch from infliximab to the biosimilar CT-P13. 20 patients reported no new side-effects or loss of disease control (80%, ±15.68). 4 patients developed side-effects after switching to CT-P13. 1 developed flu like symptoms, 1 developed inflamed foreskin and 2 developed pruritic rashes, (one patient after the first dose and the other patient after the 4th dose). All patients who developed side-effects were successfully switched back to reference infliximab. 1 patient reported loss of disease control and is due to switch back at their next infusion. None of the patients initiating CT-P13 first line have developed any side-effects to date. A paired t-test has revealed no statistically significant difference in CRP values taken before and after the switch (n=21, p=0.151). £70k is expected to be saved based on this reported use of CT-P13 in our rheumatology department over 12 months. Conclusions: In our cohort of patients, switching from Infliximab to CT-P13 appeared to be safe for the majority of patients and represents a significant opportunity to provide a more cost effective service in rheumatology. The immunogenic nature of infliximab highlights the importance of having a robust safety net strategy when switching patients to biosimilars. Further multi-centre studies are needed to corroborate our findings. References: Merck Sharp & Dohme Limited. Summary of product Characteristics for Remicade. Updated 30/10/2015. [accessed 19/01/2016] Available from http://www.medicines.org.uk/emc/medicine/3236 Committee for Medicinal Products for Human Use. Remsima EPAR Assessment report [Internet]. European Medical Agency [accessed 19/01/2016]. Available from: www.ema.europa.eu/docs/en_GB/document_library/EPAR_-_Public_assessment_report/human/002576/WC500151486.pdf /p> Disclosure of Interest: None declared